A decade of iron overload disorders and hemochromatosis: clinical and genetic findings from a specialized center in Colombia - Cristancho, L. C. Quiroga; Urbano, María Alejandra; Nati-Castillo, H. A.; Obando, María Alejandra; Gómez-Gutiérrez, Rigoberto; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2024)
Background: Iron overload disorders, including hereditary hemochromatosis (HH), are characterized by excessive iron accumulation, which can cause severe organ damage. HH is most associated with the C282Y mutation in Caucasian populations, but its prevalence and genetic profiles in Latin American populations remain underexplored.Objectives: To describe the clinical manifestations, genetic profiles, and biochemical characteristics of patients with suspected iron overload disorders in a specialized hematology center in Cali, Colombia.Methods: A retrospective observational study was conducted on 70 patients diagnosed with iron overload disorders between 2014 and 2024. Data on clinical presentation, laboratory results, imaging, and genetic mutations were collected. Statistical analyses, including chi-square tests and logistic regression, were used to evaluate factors associated with HH diagnosis.Results: Male patients constituted 64.3% of the sample, with a mean age of 56.1 years at diagnosis. Fatigue (27.1%) and joint pain (17.1%) were the most common symptoms. Of the total sample, 32.9% were diagnosed with hemochromatosis. The H63D mutation was the most prevalent (52.2%), while the C282Y mutation was rare. A predominance of both slight (100.0%) and limitrophe (58.3%) iron overload was identified among patients with hemochromatosis (p=0.036).Colombian patients with iron overload disorders show clinical, epidemiological, and biochemical profiles consistent with global patterns, yet exhibit distinct genetic diversity. Notably, they have a low prevalence of the C282Y mutation and a higher prevalence of the H63D mutation, differing from European HH profiles. Despite elevated ferritin and transferrin saturation, no significant clinical symptoms were observed, suggesting potential delays in diagnosis. These findings highlight the need